2019
DOI: 10.1016/j.shaw.2019.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Occupational Category With Risk of Physical and Mental Health Problems

Abstract: ObjectivesWe evaluated the physical and mental health problems of waged workers in Korea who had different classes of occupation.MethodsWe used data from the Korean National Health and Nutrition Examination Survey (2007–2017) to examine 22,788 workers who were waged employees and categorized these workers into 5 occupational classes.Results“Unskilled manual workers” were more likely to be older, less educated, have lower monthly income, and work fewer hours per week. Among men and relative to “managers and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Therefore, certain interventional measures can be taken into account to reduce such problems. In this regard, a number of suggestions are made here as follows: (1) Offering regular training and practical courses to better manage stress, (2) establishing a psychological consultation center only for nurses to improve their health and reduce stress and anxiety, (3) encouraging higher level managers and supervisors to create a more friendly, supportive, and collaborative environment to support the nursing staff morally. In this respect, some studies revealed that the reduced support from head-nurses can be a stress and anxietyprovoking factor in nursing work environment (3), (4) Avoiding intensive and unstandardized work shifts or employing more nurses can help in lowering stress level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, certain interventional measures can be taken into account to reduce such problems. In this regard, a number of suggestions are made here as follows: (1) Offering regular training and practical courses to better manage stress, (2) establishing a psychological consultation center only for nurses to improve their health and reduce stress and anxiety, (3) encouraging higher level managers and supervisors to create a more friendly, supportive, and collaborative environment to support the nursing staff morally. In this respect, some studies revealed that the reduced support from head-nurses can be a stress and anxietyprovoking factor in nursing work environment (3), (4) Avoiding intensive and unstandardized work shifts or employing more nurses can help in lowering stress level.…”
Section: Discussionmentioning
confidence: 99%
“…The type of job is a key social determiner of health, which can affect individuals' physical and psychological health statuses [1]. Nursing, as a stressful profession, is associated with a high level of skeletal/muscular stress, and psychologically speaking, it requires a high level of consciousness to respond to patients' and their families' medical needs as well as their key questions [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Employees in manual (or blue-collar) occupations than non-manual occupations are more likely to experience a variety of deleterious work factors such as greater job-strain, lack of social support, occupational mobility, job insecurity, physical/chemical/ergonomic hazards at work, and low wage income, which may cause occupational health disparities [ 16 , 17 , 18 ]. Several studies have shown that manual workers are vulnerable to poorer physical (e.g., cardiovascular disease, musculoskeletal pain, sickness absence) and mental health condition (e.g., stress, depression, suicide ideation) than non-manual workers [ 19 , 20 ]. There is evidence indicating the role of occupation in subsequent cognitive deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that medical radiation staff over 30 years old were more likely to develop job stress, and a similar development was observed for radiation working years, which was in agreement with a previous report of radiographers in Jordan [ 26 ]. Ahn et al [ 46 ] showed that exposure to occupational hazards adversely affects individuals’ health and exacerbates job insecurity. Thus, the increase of radiation working years aggravated the occupational psychological burden of medical radiation staff.…”
Section: Discussionmentioning
confidence: 99%